The transformation of indoctrination traditions in islamic boarding school education institutions: An islamic perspective from the quran - Amik Tri Istiami (Balai Diklat Keagamaan Ambon, 2025)
The learning model in pesantren (Islamic boarding schools), which is characterized by cultural indoctrination, leads to a very slow transformation process towards a critical pedagogy model. The impact on students includes a lack of independent thought and rationality, as well as a decline in critical and creative thinking skills. Research conducted in three Pesantren on the Island of Java indicates that Pesantren Tebuireng represents a fully integrated model. Pesantren Baitul Hikmah is undergoing a selective integration transformation model. In contrast, Pesantren Ngruki follows an instrumental integration transformation model. There are five parameters used as indicators of educational transformation: leadership transformation, education system transformation, curriculum transformation, teaching method transformation, and transformation in the level of student rationality and creativity. Ideally, Islamic educational institutions, such as pesantren, should aim to develop skills, foster rational thinking, and uphold morality grounded in religious knowledge. The purpose of this study is to examine the transformation process of spiritual learning models from indoctrinative to critical, analytical, and rational models in three pesantren in Java. This study is a descriptive, qualitative investigation that employs descriptive analysis as its method. The study concludes that among the three pesantren, only Pesantren Tebuireng has undergone a significant transformation from an indoctrinative learning model to a critical pedagogy. Meanwhile, changes at Pesantren Baitul Hikmah and Ngruki remain insignificant.